Pemanfaatan Buku KIA oleh Orangtua untuk Pemantauan Kesehatan Bayi Balita di Desa Penfui Timur - Matje Meriaty Huru (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
The low knowledge and attitude of parents about the benefits of the MCH handbook is an obstacle in the utilization of maternal and child health services. This study aimed to determine the utilization of the MCH handbook by parents to monitor the health of infants under five. This study applied a cross-sectional design. This study involved 156 parents of toddlers living in East Penfui Village, who were selected using a proportional random sampling technique. The independent variables were the knowledge and attitude of parents, while the dependent variable was the use of the MCH handbook. Data collection was done through filling out a questionnaire. Data were analyzed by Chi-square test. The results of the analysis showed that the value was 0.006 for the knowledge factor and 0.000 for the attitude factor. Furthermore, it was concluded that there was a significant relationship between knowledge and attitudes of parents and the use of the MCH handbook for monitoring the health of infants under five.Keywords: utilization of the MCH handbook; monitoring the health of infants under five; knowledge; attitude ABSTRAK Rendahnya pengetahuan dan sikap orangtua tentang manfaat buku KIA menjadi kendala dalam pemanfaatan pelayanan kesehatan ibu dan anak. Penelitian ini bertujuan untuk mengetahui pemanfaatan buku KIA oleh orangtua untuk memantau kesehatan bayi balita. Penelitian ini menerapkan rancangan cross-sectional. Penelitian ini melibatkan 156 orangtua balita yang berdomisili di Desa Penfui Timur, yang dipilih menggunakan teknik proportional random sampling. Variabel independen yaitu pengetahuan dan sikap orangtua, sedangkan variabel dependen yaitu pemanfaatan buku KIA. Pengumpulan data dilakukan melalui pengisian kuesioner. Data dianalisis dengan uji Chi-square. Hasil analisis menunjukkan nilai adalah 0,006 untuk faktor pengetahuan dan 0,000 untuk sikap. Selanjutnya disimpulkan bahwa ada hubungan yang bermakna antara pengetahuan dan sikap orangtua dengan pemanfaatan buku KIA untuk pemantauan kesehatan bayi balita.Kata kunci: pemanfaatan buku KIA; pemantauan kesehatan bayi balita; pengetahuan; sikap